2016
DOI: 10.1002/cctc.201601047
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of Titania‐Supported Bismuth Oxyiodide Heterostructured Nanofibers with Highly Exposed (1 1 0) Bismuth Oxyiodide Facets for Enhanced Photocatalytic Activity

Abstract: Bismuth oxyiodide/titanium dioxide (BiOI/TiO2) heterostructured nanofibers with exposed (1 1 0) BiOI facets were synthesized by electrospinning and hydrothermal methods. The BiOI/TiO2 heterostructures with exposed (1 1 0) BiOI facets exhibited an enhanced photoreactivity, for which the methylene blue and phenol degradation rate is increased by more than two times and the photocurrent density is 12 times as high as that of BiOI with exposed (1 1 0) facets. EPR spectroscopy indicated that the hydroxyl radicals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…As found by the valence band XPS measurements, the BiOI valence band lies 1.7 eV above that of TiO 2 ,a nd hence the conduction band minimum lies at av alue of (1.7 + E g )a bove the TiO 2 valenceb and. [27,48] This heterojunction has recently been shown by scavenginge xperiments carried out by Luo et al [56] to degrade organic speciesv ia the formation of the superoxide and hydroxyl radicals under visiblel ight as shown in Figure7.T he formationo fap-n junction is advantageous in drivingp hotoexcited electrons and holes away from one another at the interface between two materials, improving charge separation and therefore photocatalytic activity.A s such we have established that the energetics of the BiOI-TiO 2 heterojunction allows both the absorption of visible light, and am echanism for chargeseparation across the interface. Therefore, electrons excited by visible light incident upon BiOI have a0 .7 eV driving force to separatef rom their corresponding holes by transport across the TiO 2 -BiOI interface.…”
Section: Band Alignment and Mechanismmentioning
confidence: 92%
See 2 more Smart Citations
“…As found by the valence band XPS measurements, the BiOI valence band lies 1.7 eV above that of TiO 2 ,a nd hence the conduction band minimum lies at av alue of (1.7 + E g )a bove the TiO 2 valenceb and. [27,48] This heterojunction has recently been shown by scavenginge xperiments carried out by Luo et al [56] to degrade organic speciesv ia the formation of the superoxide and hydroxyl radicals under visiblel ight as shown in Figure7.T he formationo fap-n junction is advantageous in drivingp hotoexcited electrons and holes away from one another at the interface between two materials, improving charge separation and therefore photocatalytic activity.A s such we have established that the energetics of the BiOI-TiO 2 heterojunction allows both the absorption of visible light, and am echanism for chargeseparation across the interface. Therefore, electrons excited by visible light incident upon BiOI have a0 .7 eV driving force to separatef rom their corresponding holes by transport across the TiO 2 -BiOI interface.…”
Section: Band Alignment and Mechanismmentioning
confidence: 92%
“…This process, known as self-sensitisation is often overlooked in the literature but can be very significant,i ndeed in our previousw ork we found that it can be the differenceb etween af unctioning and nonfunctioning photocatalyst. We note that our study was performed [52] reverse microemulsion 250 Wh alogen lamp (> 420 nm) methylo range0.8699h À1 (14.5 10 À3 min À1 )L iu et al [53] electrospinning &s olvothermal 500 WX elamp(> 400 nm) methylene blue 0.015min À1 Zhang et al [54] electrospinning &hydrothermal 500 WX elamp(> 420 nm) methylene blue 83 %d egradationi n1 80 mins Luo et al [56] using an immobilised film suitable for practical recycling and used am uch lower-power light source than the other studies. In view of this, the best photocatalyst film (5xBiOI) wass elected from this initial screening for further testing upon the photobleaching of the UV only absorbing organic pollutant 4-chlorophenol( 4-CP) (Figure 9b).…”
Section: Photocatalytic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] In the past decades, exploring advanced strategies to enhance e-h separation, including morphological manipulation, crystal facets regulation as well as semiconductor recombination etc, are the hotpots of researches for photocatalysis technology. [14][15][16][17][18][19] Recently, designing alloyed semiconductors has become an exciting research area for constructing highly active new photocatalysts due to the unique influence of alloying characteristics on the geometry structure and electronic distribution. [20,21] Bismuth-based ternary oxide photocatalysts, bismuth oxyhalides (BiOXs, X=Cl, Br, I), are the typical visible light photocatalyst and have excellent catalytic activity than other materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to further improve the photocatalytic activity for practical applications. Up to now, some strategies have been proposed to improve the photocatalytic activity of BiOI, 23,24 such as modi¯ed by noble metals, 25 constructed the heterojunctions, 26,27 crystal-facet control [28][29][30] and sensitizer. 31 Biomass carbon quantum dots (CQDs), as a new carbon nanomaterial, has been widely used as an efcient component in design of photocatalyst owing to its excellent characteristics, such as chemical stability, low toxicity, unique edge e®ects and quantum con¯nement.…”
Section: Introductionmentioning
confidence: 99%